Pronomina Bahasa Minangkabau dalam Interaksi Jual Beli di Pasar Ibuh Kota Payakumbuh - Fauzi Hendri; Agustina (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This research was conducted to describe (1) the types of pronouns, and (2) the categorization of pronouns used by the community in buying and selling interactions at Ibuh Market, Payakumbuh City. This type of research is qualitative research using descriptive methods. The subject of this study is a word that is a pronoun in the interaction of buying and selling at the Ibuh market in Payakumbuh City. The following steps were used to analyze the data collected in this study:(1) transcribing existing data from various sources into written language, namely field observation data, (2) classifying forms of swearing based on function and type, (3) analyzing data according to research objectives, and (4) formulating research findings. Based on data analysis, there are three research findings. First, based on the results of this study, a total of 58 data were found that were pronouns in the interaction of buying and selling at the Ibuh market in Payakumbuh City, with the following details. Second, two types of Minangkabau language pronouns were found in buying and selling interactions at the Ibuh market in Payakumbuh City: (1) inactive pronouns, which consist of first personal pronouns such as crew, ambo, denai.... etc., second charm pronouns such as Ibuk, Apak, Uni, Uda.. etc., and third charm pronouns such as liau, nyo, and (2) inactive pronouns, consisting of si au, sia, surang-surang. Third, two categories of Minangkabau language pronouns were found in buying and selling interactions at the Ibuh market in Payakumbuh City: (1) intratextual pronouns, which consist of anaphoric (the antecedent positioned before the pronoun) and cataphoric in nature, namely the antecedent positioned after the pronoun; and (2) extratextual pronouns, which are antecedents outside the text.